The Sasanian Simorgh and Its Reflections in Islamic and Byzantine Art - Fathi, Seyed Salam (European Scientific Journal, ESJ, 2025)
The Simorgh, a prominent composite creature in ancient Iranian mythology and art, achieved its most stylized and symbolic form during the Sasanian period. A mythological hybrid with canine or leonine heads, eagle wings, scaled bodies, and peacock-like tails, it became a key motif in Sasanian luxury arts. This study introduces a new typology of the Sasanian Simorgh based on a comparative formal analysis of its visual variations in silk textiles, silverware, and architectural ornamentation. Four main morphological groups are identified, each defined by distinctive tail structures and compositional elements. Employing Panofsky’s iconological method in conjunction with the theories of Hans Belting and Michael Baxandall on visual transmission, the research explores how the Simorgh motif was recontextualized in Islamic and Byzantine art. The findings demonstrate how the proposed typology enhances our understanding of the Simorgh’s visual transmission across cultural and temporal boundaries, revealing consistent patterns of adaptation and transformation in Islamic and Byzantine art. This typological framework thus contributes to broader discussions on image circulation, visual hybridity, and cultural exchange in Late Antique and Byzantine visual cultures.